A bibliometric analysis of simulation-based learning in medical education: trends, gaps, and future directions - Alblooshi, Afaf Sulaiman; AlMarzooqi, Falah Mohammed; Almansoori, Taleb Mohammed; Ahmed, Gamila; Al-Shamsi, Saif; AlRadini, Faten Abdullah (Frontiers in Medicine, 2026)
BackgroundSimulation-based medical education (SBME) has become a cornerstone of modern healthcare training, enhancing clinical competence, decision-making, and patient safety. This study presents a bibliometric analysis of SBME literature from 2001 to early 2025, aiming to map publication trends, key contributors, thematic developments, and global research collaboration.MethodsA systematic search was conducted in Web of Science, Scopus, and PubMed. A total of 613 articles were screened, with 520 included for analysis. The Bibliometrix R package was used for trend analysis, author productivity, keyword co-occurrence, and collaboration network mapping.ResultsSBME publications showed significant growth, peaking in 2024. Key contributors include Schijven M and Cook DA. Major research themes shifted from technical skill acquisition to non-technical competencies and technology-enhanced learning, including virtual reality and AI. Co-occurrence analysis revealed distinct thematic clusters and rising global collaborations, though disparities persist, particularly in underrepresented regions. A noted decline in 2025 output reflects partial-year data and is included only for context rather than trend interpretation.ConclusionSBME research has evolved rapidly, driven by technological advances and global health priorities. Continued investment in equitable access, interdisciplinary collaboration, and outcome-based studies is vital to fully realize the transformative potential of simulation in medical education.